Designing optimal vitamins intake to maintain a healthy diet using weighted goal programming / Maznah Banu Habiboo Raman ... [et al.] - Habiboo Raman, Maznah Banu; Asaad, Nisa Asillah; Mazlan, Mas Atiqah Izni; Wan Nazarudin, Wan Nur Iffah Syazwanie (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Eating a healthy diet contributes to preventing future illness and improving quality and length of life. The right and sufficient vitamin through the diet is needed in order to maintain a healthy lifestyle. There is a condition called hypervitaminosis which is an acute emerging pathological condition of the body due to excess accumulation of any of the vitamins (Roop, 2018). The aim of this study is to prevent hypervitaminosis among people and minimize the total cost of vegetables since the cost of spending the vitamin is also one of the factors that influences the intake of vegetables. Based on the price of the results of some interviews, the number of fruit and vegetable intake has increased among the subjects if the price of fruits and vegetables is low (Sameeha, Shahimi & Abdul Karim, 2018). This study has introduced one of the ways on how to identify the optimal vitamin intakes using weighted goal programming.